Genetic Diversity and Phylogenetic Relationships of Pometia pinnata Variants from South Sumatra Using RAPD Markers - Hanum, Laila; Novira, Sandra; Oktariansyah, Yadi (Jurnal Biologi Tropis, 2025)
Matoa (Pometia pinnata J.R. & G. Forst) is a tropical tree of the Sapindaceae family widely distributed in Southeast Asia, yet the genetic diversity and evolutionary relationships among its variants in South Sumatra remain poorly understood. This study aimed to clarify the genetic structure of four local variants forest, red, yellow, and green matoa using Random Amplified Polymorphic DNA (RAPD) markers. Leaf samples representing each variant were collected across different regions of South Sumatra and analyzed through standard molecular procedures, including DNA extraction and RAPD amplification using five primers. Cluster analysis based on Jaccard’s coefficient and UPGMA revealed two major genetic groups, indicating substantial variation among the studied variants. Red and yellow matoa showed the closest genetic affinity, whereas forest matoa was the most distinct from the others. These findings demonstrate considerable intraspecific diversity within matoa populations in South Sumatra. The study provides essential baseline information that strengthens conservation strategies, supports potential breeding programs, and enhances understanding of the species’ evolutionary patterns within tropical ecosystems.